Kegiatan Humas PT Kereta Api Indonesia (Persero) dalam Meraih Penghargaan di Masa Pandemi - Shabilla Restu Yuniawatie; Maman Chatamallah (UNISBA Press, 2022)
Abstract. The decline in passenger volume due to the spread of the delta variant of Covid-19 has become a crisis for PT Kereta Api Indonesia (Persero) that needs to be addressed. Through this research, the researcher aims to find out and examine what PR activities are carried out by PT Kereta Api Indonesia (Persero) PR to successfully deal with the crisis so that it can win the Best Crisis Management award with Diamond predicate in The 3rd Asean PR Excellence Awards 2021. This research using a qualitative method with a case study approach. Data collection techniques used are interviews, observations, and written sources. This research will examine the process of PR activities of PT Kereta Api Indonesia (Persero) which is associated with the PR Operational Process Theory from Cutlip, Center, and Broom in Yulianita (2012). In the public relations activities carried out, PT Kereta Api Indonesia (Persero) Public Relations carries out the stages of the PR Operational process, namely Defining Public Relations Problems, Planning and Programming, Taking and Communicating, Evaluating the Program so that the activities carried out successfully handle the crises faced and produce awards in the future. pandemic. The research subjects were three people who were Manager of External Relations, Assistant Manager of External Relations, and Executor of Web Corporate, BUMN Portal and Social Media who were responsible for the continuity of the PR activities. Abstrak. Penurunan volume penumpang akibat penyebaran Covid-19 varian delta menjadi krisis bagi PT Kereta Api Indonesia (Persero) yang perlu ditangani. Melalui penelitian ini, peneliti bertujuan untuk mengetahui dan mengkaji kegiatan PR kegiatan apa yang dilakukan oleh PR PT Kereta Api Indonesia (Persero) untuk berhasil menghadapi krisis sehingga dapat meraih penghargaan Best Crisis Management predikat Diamond dalam ajang The 3rd Asean PR Excellence Awards 2021. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Teknik pengumpulan data yang dilakukan adalah wawancara, observasi, dan sumber tertulis. Dalam penelitian ini akan diteliti mengenai proses dari kegiatan PR PT Kereta Api Indonesia (Persero) yang dikaitkan dengan Teori Proses Operasional PR dari Cutlip, Center, dan Broom dalam Yulianita (2012). Dalam kegiatan humas yang dilakukan, Humas PT Kereta Api Indonesia (Persero) menjalankan tahapan proses Operasional PR yaitu Defining Public Relations Problem, Planning and Programming, Taking and Communicating, Evaluating the Program sehingga kegiatan yang dilakukan berhasil menangani krisis yang dihadapi dan membuahkan penghargaan di masa pandemi. Subyek penelitian berjumlah tiga orang yang merupakan Manager External Relations, Assistant Manager External Relations, dan Pelaksana Web Corporate, Portal BUMN and Social Media yang bertanggung jawab atas keberlangsungan kegiatan PR tersebut.